In it together?: Exploring solidarity with frontline workers in the United Kingdom and Ireland during COVID‐19. (12th September 2022) - Kinsella, Elaine L.; Muldoon, Orla T.; Lemon, Sarah; Stonebridge, Natasha; Hughes, Samantha; Sumner, Rachel C.
Abstract: The phrase 'in it together' has been used liberally since the outbreak of COVID‐19, but the extent that frontline workers felt 'in it together' is not well understood. Here, we consider the factors that built (or eroded) solidarity while working through the pandemic, and how frontline workers navigated their lives through periods of disconnection. Semi‐structured interviews with 21 frontline workers, across all sectors, were conducted in the United Kingdom and Ireland. The qualitative data were analysed systematically using reflexive thematic analysis. The three themes identified in the data were: (1) Solidarity as central to frontline experiences; (2) Leadership as absent, shallow and divisive: highlighting 'us‐them' distinctions and (3) The rise of 'us' and 'we' among colleagues. Our research offers insights into how frontline workers make sense of their experiences of solidarity and discordance during the first year of the COVID‐19 pandemic, with relevance for government and organizational policy‐makers shaping future conditions for frontline workers.